2007
DOI: 10.1016/j.tins.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 and retinoid X receptors: crucial factors in dopamine-related neuroadaptation

Abstract: Dopaminergic systems in the brain adapt in response to a variety of stimuli from the internal and external world, but the mechanisms underlying this process are incompletely understood. In recent years, evidence has emerged that certain types of transcription factor of the nuclear receptor family, specifically Nur77 and retinoid X receptors, play an important role in the Nuradaptation, and importantly, in the homeostatic regulation, of dopaminergic systems. These findings call for a reassessment of our fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 72 publications
2
65
0
1
Order By: Relevance
“…C-fos and Nur77 are immediate early genes that rapidly respond to changes in cell activity. Both genes transform acute cellular events into lasting changes in cell function by regulating the transcription of late-onset genes (Levesque and Rouillard, 2007;Robertson et al, 1991). Thus, our findings indicate that continuous exposure to antipsychotic medication induces lasting changes in both the behavioral and neurobiological impact of amphetamine.…”
Section: Discussionmentioning
confidence: 70%
“…C-fos and Nur77 are immediate early genes that rapidly respond to changes in cell activity. Both genes transform acute cellular events into lasting changes in cell function by regulating the transcription of late-onset genes (Levesque and Rouillard, 2007;Robertson et al, 1991). Thus, our findings indicate that continuous exposure to antipsychotic medication induces lasting changes in both the behavioral and neurobiological impact of amphetamine.…”
Section: Discussionmentioning
confidence: 70%
“…Second, modulations of Nur77 expression can be observed after chronic denervation and prolonged dopamine replacement therapy, indicating that these modulations do not desensitized over time. Third, by promoting the formation of the Nur77/RXR transcriptional complex (Lévesque and Rouillard, 2007), Nur77 can be viewed as a molecular switch that renders the striatum responsive to RXR agonists, making Nur77-dependent transcriptional activity and RXR an attractive new pharmacological entity aims to control LIDs. We have shown that Nur77 gene ablation alters the modulation of striatal neuropeptides, like neurotensin, normally observed following denervation and L-DOPA therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Basal levels of Nur77 are found in most of dopaminoceptive structures such as the striatum, nucleus accumbens, olfactory tubercle and prefrontal cortex (Xiao et al, 1996;Zetterström et al, 1996b). Its expression is strongly modulated after manipulation of dopamine neurotransmission, for review see (Lévesque and Rouillard, 2007). Unilateral denervation induced by local injection of 6-hydroxydopamine (6-OHDA) in rats produces a complex regulation of Nur77 in the striatum (St-Hilaire et al, 2005;St-Hilaire et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The RXR heterodimerizes with Nurr1, and promotes differentiation and survival of dopamine neurons, and modulates dopamine synthesis and function during both development and adult life [30,40,41]. Interactions of RXR and Nur77 also modulate dopaminergic function [20].…”
Section: Introductionmentioning
confidence: 99%